2006
DOI: 10.12968/bjnn.2006.2.1.20501
|View full text |Cite
|
Sign up to set email alerts
|

A study of the burden of caring for patients with amyotrophic lateral sclerosis (MND) in Japan

Abstract: Objective: The purpose of this study was to explain the experiences of caregivers of patients with amyotrophic lateral sclerosis (ALS) receiving invasive ventilation in Japan. Methods: Subjects were 12 primary caregivers of ALS patients receiving invasive ventilation. Subjects were selected by theoretical sampling. Semi-structured interviews were undertaken with each subject. The data were analyzed using a grounded theory approach. Results: Caregivers tried to ‘find a meaning in prolonging life,’ which represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…In addition, previous research has reported on problem behavior, such as delirium, in patients with PD [23], the emotional effect of the heritability of SCD [30], the multitude of different symptoms of MSA DEL id="del69" orig=","; [31], and respirator-dependent patients and burden of caregiving [27]. Further study including these diseasespecific topics would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous research has reported on problem behavior, such as delirium, in patients with PD [23], the emotional effect of the heritability of SCD [30], the multitude of different symptoms of MSA DEL id="del69" orig=","; [31], and respirator-dependent patients and burden of caregiving [27]. Further study including these diseasespecific topics would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…However, a quantitative evaluation of the care burden and depression among caregivers of individuals with intractable neurological disease has not been conducted in Japan. In addition, although the care burden and quality of life of caregivers for patients with PD [13,14,23,24] and ALS [25][26][27][28][29] have been well investigated worldwide, little research has been done on caregivers for patients with SCD and MSA until now [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Both NIPPV and LTMV increase survival time for people with MND, leading to an extended period of caregiving (33,35). Studies in the U.S., Japan and Germany point to the particular role of LTMV in caregiver burden, stress and distress (21, 35,36). Burden was reported in relation to how LTMV caregivers often become acutely aware of their responsibility for the survival of their family member, from managing the tracheostomy and suctioning the airway, to managing equipment and arranging back-up power sources.…”
Section: Assisted Ventilationmentioning
confidence: 99%
“…At the end of life, as family caregivers lose the ability to interact with their loved ones, they begin to struggle with meaning and feel powerless (36). Pagnini (37) Australian study demonstrated that MND family caregivers are at risk of prolonged grief (42).…”
Section: End-of-life Caregiving and Requests For Hastened Deathmentioning
confidence: 99%
“…Our previous study, Outcomes Research of Specific Diseases (PI: S. Fukuhara), was conducted under the auspices of the Japanese Ministry of Health, Labor and Welfare to investigate the feelings of burden among caregivers of patients, mostly with ALS, and identify those burdens related not only to time constraints and depression, as conventionally noted, but also to the difficulty in finding meaning in prolonging a patient's life and to difficulties in receiving public nursing services [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%